World Christianity and Religions 2022: A Complicated Relationship - Zurlo, Gina A. (International bulletin of mission research, 2022)
This article marks the thirty-eighth year of including statistical information on World Christianity and mission in the International Bulletin of Mission Research. This year it includes details on the growth of world religions, increasing religious diversity, and personal contact between Christians and people of other religions. The world is becoming more religious, and the world’s countries have become more religiously diverse, yet Christians have inadequate personal contact with members of other religions. Solidarity, including friendship, love, and hospitality, is posited as the way forward in addressing these trends.